Jonathan Edwards's Sinners in the hands of an angry God : a casebook - Edwards, Jonathan, 1703-1758 (Yale University Press, 2010)
Designed specifically for the classroom, this volume presents the accurate and definitive version of Sinners, accompanied by the tools necessary to study and teach this famous American sermon. With an introduction aimed at students and teachers and commentary that draws on fifty years of team editorial experience of Yale's Works of Jonathan Edwards, it provides both context and interpretation, and addresses the concerns and questions of a twenty-first century audience. The book contains questions for in-class discussion, a chronology of Edwards's life, and a glossary. In addition, curricular materials and video mini-presentations are available on a dedicated Web site. This casebook represents a innovative contribution to the art of teaching Edwards to a new generation of readers.